The potential of plant protease enzymes as rennet alternatives for developing halal cheese product: A review - Daris, Ummi Syahda; Rahmatika, Ummi Halimah; Fitri, Angel Kurnilah (Journal of Halal Science and Research, 2024)
Cheese, a derivative of dairy products made using the enzyme rennet, has received full attention because of the critical point for halalness from the milk coagulation process, which uses the rennet enzyme. Rennet enzymes can be obtained from the stomachs of animals such as cows, pigs, and goats, and they can also be produced from microbes. This very high risk of haram sources or unclean contamination has led to the development of cheese products using plant protease enzymes as a substitute for rennet enzymes. This study aims to highlight plant protease enzymes, characterize the enzymes produced, characterize cheese produced, and the potential of plant protease enzymes in replacing Rennet. Plants that have protease enzymes, such as noni, papaya, pineapple, red ginger, strawberries, pears, biduri, moringa, kiwi, tamarillo, and many other plants, have the potential to replace the rennet enzyme in making cheese. Thus, the doubts (mashbooh) arising from making cheese can be avoided by developing products from raw materials with guaranteed halal quality. Plant ingredients that can replace the rennet enzyme in making cheese are many and varied, for example, noni, papaya, moringa, bidi, pineapple, red ginger, kiwi, tamarillo, pears, Balanites aegyptiaca, strawberries, and many more. Doubtless, the problem of making cheese with Rennet can be avoided by developing cheese products from raw materials guaranteed to be halal. Limitations to plant protease enzymes on cheese production only apply to soft cheese, while it is difficult to produce hard cheese from plant enzymes.